THE LIBERAL CRITIQUES OF DEMOCRACY FROM TOCQUEVILLE TO HERMANN-HOPPE - Zoltán Pető (Srpska Politička Misao)
In my article I would like to analyze a tradition created by Alexis de Tocqueville which Erik von Kuehnelt-Leddihn called true liberalism. According to this political theory, liberty and equality do not complement each other but are in fact contradictions. In my lecture I would like to analyze how the words “democracy” and “liberty” were evaluated in the texts of the early liberals, how and why they began to be equated with each other. In this article, I will examine three representatives of this tradition in more detail: James Fitzjames Stephen, Erik von Kuehnelt-Leddihn, and Hans-Hermann Hoppe.In the modern age – argue the liberal critiques of democracy – the lack of freedom is manifested evidently. Liberty was first eradicated by royal absolutisms and then by successive democratic revolutions. As a result, the vacuum created was replaced by the modern state with Weberian “bureaucratic authority.” Modern state bureaucracy overwhelmed all sorts of public bodies, ordinances, provinces and other liberties for the sake of the abstract concept of “liberty.” On the one hand, this was done in the name of equality proclaimed on the basis of parliamentary popular sovereignty, and on the other hand it was a product of totalitarianism. of the result these processes in the modern world – while liberty is constantly being eulogized and has been raised to the rank of an official ideology – there is actually less freedom than in any previous era.